(untitled) (TSUL LEGAL REPORT, 2026)
In this article, the author analyzed the functions of state financial control and the categories related to state financial activities. The purpose of this study is to develop proposals and conclusions aimed at improving the functions of state financial control and state financial activities as a result of the study. The function of state financial control is the main activity arising from the tasks of state financing. The financial activity of the state plays an important role in these processes. In order to finance the state, it is necessary to systematically and purposefully carry out state financial control, which, in turn, leads to an open and transparent formation of the state budget. The existence of the state is linked to the extent to which its activities are funded. For example, all state revenues should be reflected in the State Budget and special funds. Tax and non-tax payments levied on the state’s income should be reflected in these funds. In these processes, state financial control is manifested; in particular, control over the processes of accumulation, distribution, redistribution, and use of funds is financial control at the state level. While the financial activity of the state means its participation in financial relations in the life of the state and society, state financial control means ensuring the function of state control over these cumulative financial relations aimed at ensuring discipline and legality. Through a comparative analysis of the legislation of national and foreign states, historical and legal, systemic, logical, statistical, and other methods, the concepts of the function of state financial control and state financial activity and proposals for it were developed. These proposals are used in scientific activities, lawmaking, law enforcement practice, interpretation, and improvement of national legislation.